Identifying Habitat Holdouts for High Elevation Tree Species Under Climate Change - Maxwell, Charles J.; Scheller, Robert M. (Frontiers in Forests and Global Change, 2020)
High elevation tree species are at great risk of decline under climate change—particularly in ranges below tree line where upslope movement is not possible —as warmer temperatures reduce snowpack and increase evaporative demand. Forecasting future locations of persistence is key to the conservation of those species. In this study, we had two major objectives: 1) to determine the potential decline in the extent of three montane conifers in California, USA, and 2) to assess how model resolution affected our estimates of decline and whether this could inform identifying potential holdouts. To do so, we forecast forest dynamics, disturbances, and future distributions of three montane conifer species under a changing climate in the Klamath Mountains using the LANDIS-II forest simulation model. Simulations were run under two grain sizes, 0.81 ha and 7.29 ha cells, and four GCMs representing three relative concentration pathways. The area occupied by the three montane conifers declined by the end of the 21st century, with only a few areas where the species were able to persist. Higher levels of climate forcing resulted in greater declines. Moreover, higher temperatures reduced tree regeneration although adult populations persisted despite the climate disequilibrium. Model resolution but did not alter the overall trend of decline. These species were projected to remain in only a few limited areas by the end of the century, but because these species are widely dispersed on the larger landscape, managers must consider trade-offs between local and broader conservation efforts and consider the current and potential range of these conifers throughout the west.